Pengenalan Efek Biologis dan Molekuler Pestisida pada Kesehatan Serta Upaya Meminimalisir Residu melalui Produk Pencuci Sayur - Fitria Diniah Janah Sayekti; Mastuti Widi Lestari; Yonatan Christian Arjune (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
Pesticides encompass chemical substances, microorganisms, viruses, and other agents used to control agricultural pests. Excessive use can pose risks to human health due to their toxicity. Farmers often opt for pesticides to improve crop quality and mitigate pest infestations; however, this practice has led to numerous cases of pesticide poisoning. Matesih Village, located in the Matesih District of Karanganyar, Central Java, Indonesia, enjoys a cool climate due to its position on the slopes of Mount Lawu an extinct volcano which renders the soil highly fertile and supports a local economy largely driven by agriculture. Many local farmers utilize chemical pesticides without fully realizing the associated health risks. Consequently, there is a need to raise awareness regarding the biological and molecular health effects of pesticides and to introduce methods for minimizing residues, such as the use of vegetable-washing products. The program's success was evidenced by an increase in the average score from 60.22 in the pre-test to 80.04 in the post-test, demonstrating improved participant understanding. Questionnaire results indicated high levels of participant satisfaction regarding the material presentation, product usage demonstrations, and the practical benefits applicable to daily life. The vegetable-washing product innovation serves not only as an alternative for residue reduction but also holds potential for further development as a natural-based health product.